Public-Private Partnership: The Model of Interaction of Regional Socio-Economic Systems in the Trans-Regional Space - Tikhomirov, Evgeny A.; Bykovskiy, Maxsim A.; Veselova, Natalia Y.; Mkrtumova, Irina V.; Malofeev, Ivan V.; Ryazantsev, Sergey V.; Luk’yanets, Artem S. (International Review of Management and Marketing, 2016)
Authors explore the feasibility of the model of public-private partnership in the framework of cooperation of regional socio-economic systems. The authors have disclosed basic capabilities and limitations of the use of models of public-private partnership. In the scientific revolution unsettled economic categories “virtual economy”, “network economy”, “information economy”, which opens promising areas of research. In turn, the category of “public-private partnership” (PPP) breaks new ground in understanding the nature of interaction between businesses and public authorities. The question arises, present or absent interconnection of informatization of society (and the economy) and the development of public-private partnership? What is the model of public-private partnership within the framework of interaction of regional socio-economic systems in a trans-regional space? In our study, we assume that the public-private partnership within the framework of the interaction of regional socio-economic systems in a trans-regional space - an alliance of government and business to achieve the maximum development of information society, the formation of the virtual economy and the associated virtual interaction of regional socio-economic systems in a trans-regional space. Keywords: economic cooperation, socio-economic systems, information economy JEL Classifications: P25, Z1